Nominalizations in humanities research articles in SINTA- and Scopus-indexed journals by Indonesian authors: An insight of its frequency and indexing matters - Udayana, Ida Bagus Widya; Munandar, Aris (Universitas Ahmad Dahlan, 2025)
Academic writing can be challenging for non-native speakers who do not have a linguistic sense of a particular language. Academic writing has a unique structure that differentiates it from other texts, i.e., it contains clauses modified to convey more compact information. This paper investigates nominalizations in English Humanities Research Articles (EHRAs) by Indonesian authors published in nationally and internationally indexed journals. Forty corpora of EHRAs become the data source of this paper. Specifically, 20 research articles were from a SINTA 2-indexed journal, and 20 were from a Scopus-indexed journal. This paper employs the Sketch Engine application to identify nominalization types these articles used when conveying ideas. A quantitative t-test was employed to determine the significance of nominalization frequency in these articles. The results show that the authors of EHRAs in SINTA-and Scopus-indexed journals used two categories of nominalizations. The t-test indicates no significant difference between the English nominalization in articles from Scopus- and SINTA-indexed journals. Despite no statistically significant difference, the density of the articles is affected by a small percentage of nominalization. This can be attributed to a specific insight into how Indonesian authors' writing structure is no different in these indexed journals. This implies that the authors have achieved the standard proficiency of two categories of nominalization.